Applications of polymeric nanoparticles in drug delivery for glioblastoma - Tan, Bin; Liu, Shuhan; Wang, Feng; Yu, Ying; Sun, Tianmeng (Frontiers in Pharmacology, 2025)
Glioblastoma (GBM) remains one of the most aggressive and treatment-resistant brain tumors, necessitating innovative therapeutic approaches. Polymer-based nanotechnology has emerged as a promising solution, offering precise drug delivery, enhanced blood-brain barrier (BBB) penetration, and adaptability to the tumor microenvironment (TME). This review explores the diverse applications of polymeric nanoparticles (NPs) in GBM treatment, including delivery of chemotherapeutics, targeted therapeutics, immunotherapeutics, and other agents for radiosensitization and photodynamic therapy. Recent advances in targeted delivery and multifunctional polymer highlight their potential to overcome the challenges that GBM brought, such as heterogeneity of the tumor, BBB limitation, immunosuppressive TME, and consideration of biocompatibility and safety. Meanwhile, the future directions to address these challenges are also proposed. By addressing these obstacles, polymer-based nanotechnology represents a transformative strategy for improving GBM treatment outcomes, paving the way for more effective and patient-specific therapies.